Islamic Education Strategy Of Islamic Te Levision Channels: A Comparision Of Al-Resalah And Al-Hijrah - Osama Kanaker; Zulkiple Abd Ghani (Universiti Sains Islam Malaysia, 2024)
The main concern of this paper is the Islamic education strategy of Islamic television channels. It identifies the vision, mission and objectives of al-Resalah and al-Hijrah television channels. The first objective of this paper is identify the vision, mission and objectives of al-Resalah and al-Hijrah channels. The second objective is to analyze education programs of the two channels for a week of broadcasting. The method used is qualitative content analysis. Thematic categorization of programs is conducted to find out the Islamic education programs broadcast on both channels. The major outcome of the paper is that the theme of education cannot be achieved throughout a number of programs broadcast on the screen, but it should be a continuous well-planed efforts to achieve the obligation of laid upon Muslims. Islamic education should not be randomly conducted through broadcasting a mixture of programs, but it should be based on a well-planned strategy to guaranty effective impact.